Prevalence of nasopharyngeal pneumococcal colonization in children and antimicrobial susceptibility profiles of carriage isolates. (October 2015) - Zhou, Julie Y.; Isaacson-Schmid, Megan; Utterson, Elizabeth C.; Todd, Elizabeth M.; McFarland, Michelle; Sivapalan, Janardan; Niehoff, Joan M.; Burnham, Carey-Ann D.; Morley, S. Celeste
Highlights: The prevalence of pneumococcal colonization in a pediatric population in the USA is 34%. The 13-valent pneumococcal conjugate vaccine (PCV13) did not alter prevalence. PCV13 did not increase the prevalence of penicillin-susceptible isolates. Summary: Nasopharyngeal (NP) pneumococcal carriage predisposes children to pneumococcal infections. Defining the proportion of pneumococcal isolates that are antibiotic-resistant enables the appropriate choice of empiric therapies. The antibiogram of NP carriage isolates derived from a pediatric population following the introduction of the 13-valent pneumococcal conjugate vaccine was defined in this study.